The effect combination of black seed (nigella sativa) and glibenclamide on blood glucose levels - Erika Martining Wardani; Riezky Faisal Nugroho (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Diabetes Mellitus was considered one of the most alarming pandemics of the twenty-first century before the advent of the COVID-19 pandemic. Glibenclamide (glyburide) is an anti-DM drug of the sulfonylurea class. Several studies have examined one of the medicinal plants, black seed (nigella sativa) as a complementary treatment in the control of DM.Objective: This study determine the effect of the combination of black seed (nigella sativa) and glibenclamide on reducing blood glucose levels.Methods: This research design was an experiment using a pretest posttest design with control group design. This study used 24 mice (mus muscullus) which were divided into 4 groups, namely a negative control group that was only given aquadest, a positive control group that was given alloxane as an induction of hyperglycemia and anti-DM drug glibenclamide, treatment group 1 was given aloxane and Black Seed, and treatment group 2 was given alloxane and a combination of black seed and glibenclamid. Data were analyzed using the Paired T Test with α = 0.05.Results: Blood glucose levels in the black seed and glibenclamid combination treatment group decreased significantly (p=0,00).Conclusion: the combination of black seed (nigella sativa) and glibenclamide is effective in lowering glucose levels.